COMPARATIVE EVALUATION OF ANTIOXIDANT AND FREE-RADICAL SCAVENGING ACTIVITY OF AQUEOUS AND METHANOLIC SPICE EXTRACTS: Life Science-Biochemistry - P. KAMLESHIYA; V.G. MESHRAM; A.H. ANSARI (International Journal of Life Science and Pharma Research, 2012)
The aqueous and crude methanolic extracts from five traditionally used spices Cinnamomum cassia, Myristica fragrans, Murraya koenigii, Piper nigrum and Trachyspermum ammi were investigated for their in-vitro antioxidant and free-radical scavenging activity by using standard methods namely reducing power assay and 2,2-Diphenly-1-picryl hydrazyl (DPPH) free-radical scavenging activity, the values are comparable to ascorbic acid.The results revealed that the tested spices shows antioxidant potential in concentration dependent manner. The methanolic extracts shows the higher percentage of free-radical scavenging activity than the aqueous extract of spices. The percent increase in reducing power assay of both the extractsof these spices was in order ascorbic acid> C.cassia> P.nigrum> M.koenigii>T.ammi>M.fragrans and the DPPH free-radical scavenging potential was found in order ascorbic acid>C.cassia>M.koenigii>P.nigrum>T.ammi>M.fragrans. Earlier studies by other workers on this aspect showed that the majority of antioxidants are phenolic compounds and their structural variants, therefore the estimation of total phenolic content will be determined by using Folinciocalteau method